Nanoparticle platform preferentially targeting liver sinusoidal endothelial cells induces tolerance in CD4+ T cell-mediated disease models - Wang, Shu-Hung; Serr, Isabelle; Digigow, Reinaldo; Metzler, Barbara; Surnov, Alexey; Gottwick, Cornelia; Alsamman, Muhammad; Krzikalla, Daria; Heine, Markus; Zahlten, Miriam; Widera, Agata; Mungalpara, Disha; et al. (Frontiers in Immunology, 2025)
IntroductionTreating autoimmune diseases without nonspecific immunosuppression remains challenging. To prevent or treat these conditions through targeted immunotherapy, we developed a clinical-stage nanoparticle platform that leverages the tolerogenic capacity of liver sinusoidal endothelial cells (LSECs) to restore antigen-specific immune tolerance.MethodsIn vivo efficacy was evaluated in various CD4+ T cell-mediated disease models, including preventive and therapeutic models of myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis (EAE), ovalbumin-sensitized delayed-type hypersensitivity (DTH), and the spontaneous type 1 diabetes model. Nanoparticle-induced antigen-specific immune responses were also analyzed through adoptive transfers of 2D2 transgenic T cells into wild-type mice, followed by nanoparticle administration.ResultsThe peptide-conjugated nanoparticles displayed a uniform size distribution (25–30 nm). Their coupling efficiency for peptides with unfavorable physicochemical properties was significantly enhanced by a proprietary linker technology. Preferential LSEC targeting of nanoparticles coupled with fluorescently labeled peptides was confirmed via intravital microscopy and flow cytometry. Intravenous nanoparticle administration significantly reduced disease severity and demyelination in EAE, independent of prednisone at maintenance doses, and suppressed target tissue inflammation in the DTH model. Furthermore, prophylactic administration of a mixture of nanoparticles coupled with five autoantigenic peptides significantly lowered the hyperglycemia incidence of the non-obese diabetic mice. Mechanistically, the tolerizing effects were associated with the induction of antigen-specific regulatory T cells and T cell anergy, which counteract proinflammatory T cells in the target tissue.ConclusionOur findings demonstrate that peptide-loaded nanoparticles preferentially deliver disease-relevant peptides to LSECs, thereby inducing antigen-specific immune tolerance. This versatile clinical-stage nanoparticle platform holds promise for clinical application across multiple autoimmune diseases.